Caracterização geoquímica marinha e avaliação do impacto das atividades antrópicas e de exploração de petróleo sobre os sedimentos da plataforma continental do estado de Sergipe e sul do estado do Alagoas - Barbosa, Ariadna Cristina Gomes (2010)
The environmental impact caused by oil, sewage, industrial, mining, leaching of soil and urban surfaces in the Brazilian coast has generated effluents mixed, with the metal trace a specific problem because they are deposited in marine sediments and present toxicity at the same time, persistence and bioaccumulation. Sediments act as operating compartment corded an essential role in the redistribution of marine biota, because that guard the historical record of contamination of water body. Oil exploration extends to offshore environment, occupying a prominent position in the energy matrix, responsible for most of the national supply. The oil and gas activities may include a significant source of pollution of the planet. The aim of this study was to observe the sediment profiles of the continental shelf off Sergipe and Alagoas southern state, checking for a variation of the concentration of trace metals according to depth. Three cores (PCM-9 (A), PCM-9 (B), Est.2 (A)) were performed to obtain a vertical profile of sediment samples obtained at various depths. In this study, drew up the metals Co, Cr, Fe, Li, Mn, Ni, Pb, Zn, Al and Cu total and partial, were determined by atomic absorption spectrometric (AAS). In the extraction part, the result of the recovery was above 90%, ranging from 92% to 111.1%. In the extraction result of the total recovery ranged from 77.6 to 99%. These values were obtained in the studied parameters, indicating good accuracy of the methodology. The values of RSD are below 10%, expressing the accuracy of methodology. Showed that the concentration distribution of trace metals in sediment profiles vary with depth. Colors in PCM-9 (A), PCM-9 (B), increased concentrations of metals and the core Est.2 (A) decreased gradually from base to surface. The iron was approved as a geochemical normalizer better. The values of the calculated enrichment factor shown to be low, considering the low enriched, except Pb, Co, Mn and Al that have moderate values. The geochemical background values were estimated in three different procedures, which can generate unrealistic characterizations of the state of pollution. The values of trace metals are below the sediment quality guidelines, which leads to the adverse effect on aquatic biota is unlikely.